2021
DOI: 10.1017/s2045796021000214
|View full text |Cite
|
Sign up to set email alerts
|

Suicide, self-harm and thoughts of suicide or self-harm in infectious disease epidemics: a systematic review and meta-analysis

Abstract: Aims Suicide accounts for 2.2% of all years of life lost worldwide. We aimed to establish whether infectious epidemics are associated with any changes in the incidence of suicide or the period prevalence of self-harm, or thoughts of suicide or self-harm, with a secondary objective of establishing the frequency of these outcomes. Methods In this systematic review and meta-analysis, MEDLINE, Embase, PsycINFO and AMED were searched from inception to 9 September 2020. Studies of infectious e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
42
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 111 publications
3
42
0
1
Order By: Relevance
“…Several analytical studies that have utilised governmental suicide databases covering the entire population reported that the impact of the COVID-19 pandemic on suicide mortality in Japan may change over time and could have various different targets [ 11 , 12 ]. In Japan, suicide mortality was steadily decreasing between 2009 and 2019, but increasing in 2020: from 20,169 (males: 14,078, females: 6091) to 20,919 (males: 13,943, females: 6976) ( Figure 1 ) [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several analytical studies that have utilised governmental suicide databases covering the entire population reported that the impact of the COVID-19 pandemic on suicide mortality in Japan may change over time and could have various different targets [ 11 , 12 ]. In Japan, suicide mortality was steadily decreasing between 2009 and 2019, but increasing in 2020: from 20,169 (males: 14,078, females: 6091) to 20,919 (males: 13,943, females: 6976) ( Figure 1 ) [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, although several studies have highlighted that the COVID-19 pandemic has heightened the risk of poor mental health, few have used national-level data to examine suicide in this period. A systematic review has warned about the low quality of the design and sampling of extant studies, 38 and studies that used nationallevel data to examine mental health burden owing to the COVID-19 pandemic [39][40][41][42] have not directly explored the reasons for suicide. This study aimed to assess which reasons for suicide had higher monthly numbers during the COVID-19 pandemic than the estimated number of suicide deaths for that month.…”
Section: Introductionmentioning
confidence: 99%
“…Otherwise, one limited study reported no effect of the pandemic on acute compulsory psychiatric admissions in Amsterdam ( van der Heide & Coutinho, 2006 ). Two recent systematic reviews on the experience of mental health during epidemics found no other literature relating to the 1918–20 influenza pandemic ( Neelam et al, 2021 ; Rogers et al, 2021 )—although the search strategies of the reviews may have been too narrow. Additionally, I am aware that two research teams have reported no connection between the pandemic and psychiatric admissions in Croatia ( Milovan Delić and Plavšić, 2020 ; Vukojević et al, 2021 ) and that Dimka and Mamelund (2020) report on the high case-fatality of medically institutionalized individuals, including psychiatric patients, in Norway.…”
Section: Discussionmentioning
confidence: 99%